1980
DOI: 10.1007/bf01757297
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and renal function during low frequency positive pressure ventilation with extracorporeal CO2 removal

Abstract: Six lambs were anesthetized and connected venovenous mode to a Membrane Lung for Extracorporeal CO2 removal. The animals underwent several hours periods of continuous positive pressure ventilation (CPPV), at 5 cmH2O positive end expiratory pressure (PEEP), alternated with several hours periods of low frequency positive pressure ventilation (5 cmH2O PEEP, 2 b.p.m.) with extracorporeal CO2 removal (LFPPV-ECCO2R). During LFPPV-ECCO2R compared with CPPV, cardiac output increased by 26%, pulmonary vascular resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…ECCO2R combined with low frequency positive‐pressure ventilation is currently used at some ARDS centers to improve the gas exchange in the most severe ARDS cases (14–20). A trend to less invasive and less risky devices is clearly visible; a complete CO 2 removal was achieved when the blood flow was as low as 700 ml · min −1 (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…ECCO2R combined with low frequency positive‐pressure ventilation is currently used at some ARDS centers to improve the gas exchange in the most severe ARDS cases (14–20). A trend to less invasive and less risky devices is clearly visible; a complete CO 2 removal was achieved when the blood flow was as low as 700 ml · min −1 (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested the possibility of removing COZ with this device and providing oxygenation with reduced ventilatory rates, thus optimizing the chances of lung recovery while providing adequate gas exchange. Further developments of this technique (20)(21)(22)(23)(24)(25) have shown that ADO can be safely performed for many days when metabolic CO2 is removed by an extracorporeal membrane lung (ECCOZR) and 100% 0 2 is supplied directly into the trachea keeping intrapulmonary pressures at 5 cmH2O (0.5 kPa). Increasing the continuous airway pressure (P,) to 20 cmH20 (2 kPa) was shown to reduce shunt, and improve oxygenation, funtional residual capacity (FRC) and compliance (22).…”
Section: Apneic Dafusion Oxygenation and Continuousjow Apneic Ventilamentioning
confidence: 99%